Humanized mice: are we there yet? - Macchiarini, Francesca (The Rockefeller University Press, 2005)
Animal models have been instrumental in increasing the understanding of human physiology, particularly immunity. However, these animal models have been limited by practical considerations and genetic diversity. The creation of humanized mice that carry partial or complete human physiological systems may help overcome these obstacles. The National Institute of Allergy and Infectious Diseases convened a workshop on humanized mouse models for immunity in Bethesda, MD, on June 13–14, 2005, during which researchers discussed the benefits and limitations of existing animal models and offered insights into the development of future humanized mouse models.